2004
DOI: 10.1128/cdli.11.2.250-254.2004
|View full text |Cite
|
Sign up to set email alerts
|

Rectal Nitric Oxide Gas and Stool Cytokine Levels during the Course of Infectious Gastroenteritis

Abstract: Nitric oxide (NO) is known to be an important inflammatory mediator with a potential role in gastrointestinal diseases. We prospectively studied the luminal NO levels in 51 patients with infectious gastroenteritis, 35 patients with nonenteric bacterial infections, and 11 healthy control subjects. The levels of proinflammatory cytokines were simultaneously measured in the stools of patients with gastroenteritis. Rectal gas was sampled with balloon catheters made of silicone and was analyzed for NO levels by che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
34
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 26 publications
1
34
0
Order By: Relevance
“…The nitrosative chemistry generated by acidified NO 2 − not only inhibits SPI2 expression (13) but also, as shown herein, S-nitrosylates SsrB. The advantage of Salmonella expressing the wild-type, RNS-responsive ssrB allele is evident in mice on an NRAMP1 R background, indicating that sensing of RNS by Cys 203 must take place within macrophages where the NRAMP1 metal transporter is expressed (26).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The nitrosative chemistry generated by acidified NO 2 − not only inhibits SPI2 expression (13) but also, as shown herein, S-nitrosylates SsrB. The advantage of Salmonella expressing the wild-type, RNS-responsive ssrB allele is evident in mice on an NRAMP1 R background, indicating that sensing of RNS by Cys 203 must take place within macrophages where the NRAMP1 metal transporter is expressed (26).…”
Section: Discussionmentioning
confidence: 99%
“…This rich biochemistry probably mediates the broadspectrum antimicrobial activity of reactive nitrogen species (RNS) against phylogenetically diverse microorganisms (1). Diarrheagenic Salmonella elicit a burst of NO in rectal content in infected humans (2) and stimulate the accumulation of iron-nitrosyl adducts in affected viscera of experimental animals (3). Mounting evidence indicates that these RNS are not mere signatures of the infection but are active components of the anti-Salmonella host arsenal.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There are no commercial assays available for measuring cytokine levels in fecal specimens. Some investigators have shown the correlation of elevated levels of IL-1␤ and IL-8 in active disease, particularly in cases of moderate to severe infection (162,166,167), with subsequent decreases in levels of these cytokines in stool when the patient recovers from acute infection (166). In a study by Jiang et al, the authors demonstrated that a single-nucleotide polymorphism (SNP) (251 A/A) in the IL-8 gene is associated with increased susceptibility to C. difficile disease (167).…”
Section: Evolution Of Testing Methodsmentioning
confidence: 99%
“…Campylobacter can invade human epithelial cell monolayers (11,12), causing disruption to the epithelium and gaining access to its basal side (41,45). Interleukin-1␤ (IL-1␤), IL-8, and nitric oxide (NO) are produced during human Campylobacter infections (10), and in vitro experiments with human-derived epithelial cell lines have shown that C. jejuni can induce the secretion of a range of cytokines and chemokines (2,3,16,17,19).…”
mentioning
confidence: 99%